Comparison of Severity in Diabetic Ulcer Patients with and Without Sepsis - Maydiana, Siti Roisya Aga; Nurhayatun, Evi; Putri, Desy Puspa (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Diabetes mellitus patients in Central Java grow yearly. According to data provided by the Central Java Health Department in 2019, Diabetes mellitus ranks second as the largest non-communicable disease (NCD), covering 13,4% of the total NCD patients. The prevalence of diabetic ulcers is 15-25% of all diabetes mellitus patients in Indonesia, which concerns the author regarding the possible increase of the diabetic ulcer population in Central Java. The severity of diabetic ulcers depends on various factors, including infection and complications. The most common complication is sepsis, a systemic infection often arising from local infections that are not appropriately treated, causing progressive damage and increasing mortality rates. This study aims to examine the comparison of ulcer severity in diabetic ulcer patients with sepsis and non-sepsis complications using Meggitt Wagner's criteria. This study utilizes an analytic observational study using a cross-sectional approach. The author sampled 126 patients diagnosed with Diabetic Ulcers in 2022 at Dr. Moewardi General Hospital for this study, using a purposive sampling method. The research was conducted by looking at the patient's medical record data, and data analysis using SPSS software. The test used in this research includes a Parametric T-independent test and a Pearson bivariate relationship test. This study shows that the comparison of ulcer severity in diabetic ulcer patients with sepsis and without sepsis was statistically significant (p-value = 0.000002). The mean of the group with sepsis (3.4127) was greater than the group without sepsis (2.5238). In conclusion, the comparison of ulcer severity in diabetic ulcer patients with sepsis and without sepsis is significant. We recommend future researchers include patients’ comorbidities, total hospitalization time, and detailed information on drug use and patient adherence to treatment in their research for more nuanced findings.